Macbeth e a adaptação do herói trágico shakespeariano no cinema - Ribeiro, Raquel Ferreira (2022)
William Shakespeare's Macbeth features a protagonist who begins the play as an honorable and respected man, but turns into a violent tyrant who brings instability to Scotland. The warrior Macbeth is among the Shakespearean characters whose plot brings him closer to the elements of the classic tragic hero than other Shakespearean tragedies. The general goal of this work is to discuss the character Macbeth as a tragic hero (Charlton, 1948; Bradley, 2009; Campbell, 2009; Wells, 2017) and to investigate the character’s adaptation for the theaters in the production Macbeth (2015) by Australian director Justin Kurzel. We present review on studies of tragedy and classical tragic element (Aristóteles, 2014; Nietzsche, 2007; Steiner, 2010; Cardoso 2005); and also about the building of Shakespearean tragic hero that can be identified in cinematographic productions. Discussions about film adaptations identify a new meaning construction, taking the director/producer as a reader of source work that adapts plot into sequences of images (Cattrysse, 2014; Bordwell, et al. 2017; Diniz, 1999; Lefevere, 2007; Hutcheon , 2013). Discussions around film adaptations reinforce the idea that the literary text does not prescribe the path to be followed by those who adapt it, so that literature serves only as a starting and not an arrival point. This type of approach attributes a creative and transformative process to the act of adapting a literary work and offers big screen audiences a new text. Throughout this work, we present concepts of Shakespearean film, Shakespearean tragedy, Shakespearean tragic hero and we analyze specific scenes that indicates the creation of those involved in Macbeth (2015) production in order to discuss a reinterpretation of Shakespearean tragic hero Macbeth in this adaptation that presents specific features of the character in a 21st century view.